(untitled) (Research, Society and Development, 2022)
Objective: This study is an integrative review research and aims to identify and analyze the scientific production of the last fifty years (2006-2021) on the psychological impacts of cancer and cancer treatment in young people. Methods: Through specific descriptors; Young Adult and Cancer and Young Adult and Cancer, seven scientific articles were selected, available in virtual databases: Google academic, Electronic Journals in Psychology (Pepsic), Scientific Electronic Library Online (SciELO). Results: In general, it is possible to point out that the diagnosis of cancer and oncological treatment are configured as remarkable experiences in the biography of young adults. Since, culturally, youth is associated with health and the construction of projects for the future, illness imposes itself on the lives of young people, requiring a reconstruction of their ways of life. There is also a greater number of studies developed by physicians and a smaller number of publications by the human and social sciences, such as Psychology. Conclusion: Despite the importance of the theme, the results point to an incipient production on the subject of the psychological impacts of cancer in young people.